GapAnalysis: An R package to calculate conservation indicators using spatial information - Ramírez Villegas, Julián Armando; Carver, Daniel; Sosa, Chrystian C.; Khoury, Colin K.; Achicanoy Estrella, Harold Armando; Díaz, Maria Victoria; Sotelo, Steven; Castañeda-Álvarez, Nora P. (2021)
Effective assessments of the current status of biodiversity conservation are needed to support planning, policy and action, from local to global levels. Of particular use would be well documented, reproducible methods based on openly accessible data and tools. Such methods should provide an accurate estimate of the state of conservation of diversity, identifying gaps in current conservation systems, while providing a benchmark against which to measure success, including determining when conservation goals have been met. Here we introduce GapAnalysis, an open source R package developed to support the assessment of the state of conservation of taxa, both ex situ (in genebanks, botanic gardens and other repositories) and in situ (in protected natural areas). The eco-geographic variation maintained in conservation repositories and that present within protected natural areas is compared with the full extent of eco-geographic variation predicted within species' native ranges. Eco-geographic conservation gaps are identified, and taxa are then prioritized for further action. The package enables users to quickly determine conservation status, gaps and priorities for as few as one to as many as thousands of taxa, for any wild flora or fauna for which occurrence data and species distribution models are available. To demonstrate the use of GapAnalysis, we provide case studies for wild plant taxa in the genera Capsicum L. and Cucurbita L, with an accompanying online R tutorial for three of the Cucurbita species.